The Hanbalite Theology: A Critical Study of The Hanbalite Theological Creeds and Polemical Adversaries - Ahwan Fanani (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
The Hanbalite school, well-known as a traditional school of Islamic law, played important role in theological disscourses in Islamic history. The fact, however, fails to be paid enough attention because of prevalent knowledge among Islamic society that the Hanbalite is only and a school of Islamic law. The Hanbalite theology is frequently abandoned in Islamic scholarship, although several researches have tried to reveal them. This article is aimed to extend previous researche of the Hanbalite theology through the description of its creeds and the elaboration of theological polemics between the Hanbalites and their adversaries. This article employs the history of idea by analyzing references written by Hanbalite scholars and other related sources. The references are collected and categorized according to the need of topics and then interpreted to provide readers with overall picture of the Hanbalite theology and their polemics along history. The Hanbalites creeds are based on textual understanding on Quranic texts and prophetic traditions. The creeds are underpinned by the idea that the Quran is not created and Quranic verses on God’s attributes should be understood textually. The idea led Hanbalite scholars to do a debate with other theologians. The article provides a more vivid description on Hanbalite creeds and analyzes the creeds in the light polemics launched by the Hanbalite scholars against their rivals. The article, however, does not elaborate detailly on each Hanbalite scholar’s contribution in forming sophisticated Hanbalite theology.